Pengembangan Pelet Komposit Biomassa-Cangkang Kerang sebagai Bahan Bakar dan Bahan Baku Alternatif untuk Co-processing Semen - Dian Prabowo; Nur Indah Wardani; Unggul Satria Jati; Andika Prastya; Ali Basroh (Infotekmesin, 2026)
This study evaluates Biomass-Shell Composite Fuel (BSCF) from lignocellulosic and seashell waste via fermentation and densification. Results show pellet moisture (2.64–11.0%) meets ISO 17225-6:2021 standards. The highest heating value was 12.11 MJ/kg in the mixed variant, though it was below the 14.5 MJ/kg minimum. Bulk density (0.12–0.37 g/cm³) and length (33–50 mm) were also below ideal standards. Incorporating seashells caused high ash content (32.16–34.84%). Consequently, BSCF pellets are recommended as an Alternative Fuel and Raw Material (AFR) for the cement industry, where mineral residues can substitute for limestone in clinker production. Optimization requires increased compaction pressure and reduced particle size to improve product efficiency.